2018
DOI: 10.1016/j.csm.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tibial and Femoral Bone Morphology on Knee Kinematics in the Anterior Cruciate Ligament Injured Knee

Abstract: Bone morphology is one feature that contributes to knee kinematics. The geometry of the tibia and femur vary across individuals, and these differences can influence the risk of anterior cruciate ligament (ACL) injury and of failure after isolated ACL reconstruction. There has been renewed interest in lateral extra-articular stabilization procedures to supplement an ACL reconstruction, although which patients benefit most from these procedures remains unclear. This article reviews the impact of bone morphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 31 publications
1
59
0
Order By: Relevance
“…There are two components of the ACL, the smaller anteromedial bundle and the larger posterolateral bundle, named according to where the bundles insert into the tibial plateau. The ACL stabilizes the range of anterior knee translation and through proprioception, and participates in the control of the correct joint kinematics (Lansdown and Ma, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There are two components of the ACL, the smaller anteromedial bundle and the larger posterolateral bundle, named according to where the bundles insert into the tibial plateau. The ACL stabilizes the range of anterior knee translation and through proprioception, and participates in the control of the correct joint kinematics (Lansdown and Ma, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated the role of lateral femoral condyle morphology in the rotation mechanism of the knee joint [12,13]. As the lateral femur rolls from its circular bending radius to its flatter part, the knee joint experiences physiologic rotational motion.…”
Section: Discussionmentioning
confidence: 99%
“…The architecture of joint shape is extensively related to the pathogenesis of osteoarthritis. Many studies have suggested that tibial and femoral bone morphology at the knee joint is a risk factor for anterior cruciate ligament (ACL) injury (Lansdown and Ma, 2018;Vasta et al, 2018) and medial meniscus tears (Barber et al, 2017), especially the tibial plateau slope (Wang et al, 2017). Not only to the susceptibility to ACL injury, post trauma recovery is also linked to the bone shape differences (Lansdown et al, 2017).…”
Section: Discussionmentioning
confidence: 99%